Medicinal Plants and their Traditional Uses - Keskin Cumali (Journal of Advances in Plant Biology, 2018)
This review surveys medicinal plants and their traditional uses, summarizing common indications and bioactive constituents. It contrasts perceived safety with evidence on efficacy and potential toxicity or interactions. The authors highlight the need for standardized preparations and controlled studies to translate ethnobotanical knowledge into safe, effective therapies.